A SiO 2 Thin film cadmium telluride power generation glass and preparation method thereof

By coating and curing the SiO2 film on the cadmium telluride power generation glass, the problem of reducing power generation efficiency caused by light reflection is solved, and the effect of improving the photoelectric conversion efficiency is achieved.

CN117712192BActive Publication Date: 2025-03-18成都莱普科技股份有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311791502.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2025-03-18
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

In practical applications, cadmium telluride power generation glass has reduced power generation efficiency due to light reflection, and its photoelectric conversion efficiency needs to be improved.

Method used

The SiO2 suspension is coated on the glossy surface of the cadmium telluride power glass, and after drying and scanning the entire CO2 laser, a SiO2 film with a thickness of 90-150 nm is formed to reduce the reflectance and improve the photoelectric conversion efficiency.

Benefits of technology

Through the curing treatment of SiO2 film, the reflectivity of the power generation glass is reduced, the photoelectric conversion efficiency is improved, and the circuit damage is avoided by traditional heating methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117712192B_ABST
    Figure CN117712192B_ABST
Patent Text Reader

Abstract

The present application discloses a cadmium telluride power generation glass with a SiO2 film and a preparation method thereof, and belongs to the technical field of power generation glass. The preparation method comprises: coating a suspension composed of nano-SiO2 particles on the light-facing surface of the cadmium telluride power generation glass mother material to form a SiO2 coating; then drying the cadmium telluride power generation glass mother material using a hot plate; then using a CO2 laser to scan the entire surface of the SiO2 coating of the cadmium telluride power generation glass mother material, and controlling the temperature at the SiO2 coating to 400‑450°C during the scanning process, so that the SiO2 coating is cured to form a SiO2 film with a thickness of 90‑150nm. The present application uses a CO2 laser scanning method to cure a layer of SiO2 film on the glass surface, which can not only effectively prevent the circuit on the backlight side of the glass from being damaged during the silicon oxide curing process, but also effectively reduce the reflectivity of the power generation glass and improve its photoelectric conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power generation glass, and in particular to a cadmium telluride power generation glass with a SiO2 film and a preparation method thereof. Background Art

[0002] Cadmium telluride power generation glass, also known as cadmium telluride thin film solar cell, is a glass substrate on which five layers of semiconductor thin film are deposited in sequence, turning the glass from an insulator into a conductor and having the function of generating electricity. This type of power generation glass has the following advantages: simple structure and low manufacturing cost; its temperature coefficient is much lower than other crystalline silicon solar cells, and it is more suitable for harsh application environments such as high temperature, deserts and supermarkets; it can generate electricity in low light environments such as early morning, evening, cloudy and rainy days, and has a longer power generation time than crystalline silicon cells. Therefore, this power generation glass has the advantages of low carbon, high power generation, high efficiency, good performance under complex environmental conditions, and beautiful appearance. It can customize light transmittance, color pattern, etc. It can be recycled after the end of its life cycle. It is a green, energy-saving, and energy-creating energy-type building material that can create value for owners and can be widely used in public buildings such as schools and hospitals, and curtain wall construction of supermarkets and factory buildings.

[0003] Although this cadmium telluride power generation glass has good weak light effect and long power generation time. However, since the cadmium telluride power generation glass generates electricity by absorbing natural light, the light will be reflected on the glass surface during the actual working process, resulting in a certain reduction in its power generation efficiency. In view of this, the present application improves the cadmium telluride power generation glass to improve its photoelectric conversion efficiency. Summary of the invention

[0004] The invention discloses a cadmium telluride power generation glass with SiO2 film and a preparation method thereof, so as to improve the above problems.

[0005] The technical solution adopted by the present invention to solve the above technical problems is:

[0006] A method for preparing cadmium telluride power generation glass with SiO2 film, comprising:

[0007] Coating SiO2 suspension on the light-facing surface of the cadmium telluride power generation glass base material to form a SiO2 coating;

[0008] Drying the cadmium telluride power generation glass mother material;

[0009] Then, a CO2 laser is used to scan the entire surface of the SiO2 coating of the cadmium telluride power generation glass mother material, and the temperature of the SiO2 coating is controlled to be 400-450°C, so that the SiO2 coating is solidified to form a SiO2 film with a thickness of 90-150nm.

[0010] Furthermore, when a CO2 laser is used to scan the entire sheet, the scanning is performed in a galvanometer manner, and the output power of the CO2 laser is 60-100w.

[0011] Furthermore, the parameters of the CO2 laser scanning are: spot width 0.15-0.25 mm; line filling spacing 0.04-0.06 mm.

[0012] Furthermore, the thickness of the above SiO2 coating is 100-200nm.

[0013] Furthermore, the coating method of the above SiO2 coating is:

[0014] Drop the SiO2 suspension on the center of the CdTe power generation glass mother material, wait until the SiO2 suspension completely infiltrates the surface of the CdTe power generation glass mother material, rotate the CdTe power generation glass mother material at a speed of 100-200 rpm for 50-70 seconds, and then rotate the CdTe power generation glass mother material at a speed of 400-600 rpm for 60-120 seconds.

[0015] Furthermore, the content of SiO2 in the above-mentioned SiO2 suspension is 8-12wt%, and the solvent is ethanol or alcohol.

[0016] Furthermore, the volume of the SiO2 suspension dripped onto the center of the cadmium telluride power generation glass matrix is ​​10-15 mL.

[0017] Furthermore, the temperature for drying the cadmium telluride power generation glass base material is 50-100° C. and the time is 8-10 minutes.

[0018] The present application also provides a cadmium telluride power generation glass, which is prepared by the above-mentioned preparation method, and the light-facing surface of the cadmium telluride power generation glass has a SiO2 film with a thickness of 90-150nm.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The cadmium telluride power generation glass provided in the present application reduces the reflectivity of the power generation glass and improves its photoelectric conversion efficiency by solidifying a layer of SiO2 film on the glass surface. Since the SiO2 coating must be solidified and bonded to the glass at a temperature above 400°C, if it is heated using traditional methods, the power generation glass will be heated together, which can easily damage the circuit at the bottom of the power generation glass, thereby causing the power generation glass to fail. In order to further overcome this problem, the present application prepares the SiO2 film by first coating a SiO2 suspension, drying it, and then using a CO2 laser to scan the entire surface of the SiO2 coating of the cadmium telluride power generation glass mother material, and during the scanning process, the temperature of the SiO2 coating is strictly controlled to be 400-450°C. Scanning in this way, the light-facing surface of the power-generating glass mother material is heated by the laser, the instantaneous temperature is higher than 400°C, and the SiO2 coating solidifies and combines with the mother material; and because the heating time is short (for a 10cm*10cm power-generating glass, the entire piece of scanning takes only 40s), the temperature of the backlight surface of the power-generating glass mother material is far below the damage threshold of 100°C, so the circuit on the backlight surface of the glass is not damaged. At the same time, low-temperature drying of the mother material before laser processing can effectively reduce the tendency of the power-generating glass to crack, and can volatilize some organic matter in the mother material, thereby improving the efficiency of laser processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A picture showing a SiO2 film formed on the surface of the cadmium telluride power generation glass disclosed in Example 1 of the present invention;

[0022] Figure 2 A film thickness test diagram of a SiO2 film formed on the surface of the cadmium telluride power generation glass disclosed in Example 1 of the present invention is shown;

[0023] Figure 3 A schematic diagram of performing CO2 laser scanning in a galvanometer manner disclosed in Example 1 of the present invention is shown;

[0024] Figure 4 The picture of the power generation glass when the SiO2 coating is cured by baking at a high temperature of 397°C in Experimental Example 1 of the present invention is shown;

[0025] Figure 5 The picture of the power generation glass when the SiO2 coating is cured by baking at a high temperature of 397°C in Experimental Example 1 of the present invention is shown;

[0026] Figure 6 A picture of the power generation glass when the SiO2 coating is cured by baking at a high temperature of 397°C in Experimental Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0027] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0028] The technical solution of this embodiment is:

[0029] A cadmium telluride power generation glass with SiO2 film, the preparation process of which comprises the following steps:

[0030] (1) Coating a SiO2 suspension on the light-facing surface of a cadmium telluride power generation glass base material to form a SiO2 coating;

[0031] Furthermore, the thickness of the SiO2 coating is 100-200nm, preferably, the coating thickness is 110-180nm, and more preferably, the thickness is 120-150nm. If the coating thickness is too thin, the SiO2 formed after curing is too thin to completely reduce the reflection; if the coating is too thick, the curing effect will be poor, and the surface hardness and wear resistance after curing will be reduced.

[0032] Preferably, the coating is carried out by spin coating; compared with the roll coating method, spin coating is conducive to the uniform diffusion of the SiO2 suspension, and the consistency of the film layer obtained after curing is better. More specifically, the coating method of the above-mentioned SiO2 coating is: drop the SiO2 suspension on the center of the cadmium telluride power generation glass mother material, wait for the SiO2 suspension to completely infiltrate the surface of the cadmium telluride power generation glass mother material, rotate the cadmium telluride power generation glass mother material at a speed of 100-200rpm for 50-70s, and then rotate the cadmium telluride power generation glass mother material at a speed of 400-600rpm for 60-120s. During the spin coating process, first use a lower speed rotation (100-200rpm) to make the suspension evenly distributed on the glass surface; then use a higher speed rotation (400-600rpm) to throw out the excess suspension so that the thickness of the suspension reaches the expected value.

[0033] More preferably, the low-speed spin coating is 55-65 seconds at 120-180 rpm, or 60 seconds at 140-160 rpm; the high-speed spin coating is 80-100 seconds at 450-550 rpm, or 90 seconds at 480-520 rpm.

[0034] Furthermore, the content of SiO2 in the SiO2 suspension is 8-12 wt% (preferably 9-11 wt%), and the solvent is ethanol. Ethanol is used as the solvent, which is easy to volatilize in the subsequent steps and is not easy to remain on the surface of the power generation glass.

[0035] Furthermore, the volume of the SiO2 suspension dripped onto the center of the cadmium telluride power generation glass matrix is ​​10-15 mL, preferably 11-14 mL.

[0036] (2) Drying the cadmium telluride power generation glass base material;

[0037] The drying here is low-temperature drying, which can dry the SiO2 coating on the surface of the cadmium telluride power generation glass mother material and volatilize some organic matter in the mother material; secondly, it can heat the mother material, thereby reducing the stress during the laser scanning process and the tendency of the glass to crack. Further, the temperature for drying the cadmium telluride power generation glass mother material is 50-100°C, preferably 50-80°C, and more preferably 60°C, 70°C or 80°C.

[0038] (3) A CO2 laser is used to scan the entire surface of the SiO2 coating of the cadmium telluride power generation glass matrix, and the temperature of the SiO2 coating is controlled to be 400-450°C, so that the SiO2 coating is solidified to form a SiO2 film with a thickness of 90-150nm.

[0039] In order to achieve a good curing effect of SiO2 coating, the temperature of SiO2 coating needs to be at least greater than 400℃. At the same time, in order to avoid excessive temperature and damage to the internal circuit of the power generation glass, the temperature of SiO2 coating needs to be controlled at 400-450℃. Since SiO2 absorbs laser with a wavelength of 10064nm well, CO2 laser is used to scan the surface of the base material completely with laser.

[0040] Furthermore, when a CO2 laser is used to scan the entire sheet, the scanning is performed in a galvanometer manner, and the output power of the CO2 laser is 60-100w, preferably 70-90w, and more preferably 80w. By controlling the output power of the CO2 laser, the temperature at the SiO2 coating during scanning can be effectively controlled to be 400-450°C. Preferably, the parameters of the CO2 laser scanning are: spot width 0.15-0.25mm (preferably 0.17-0.23mm); line filling spacing 0.04-0.06mm (preferably 0.045-0.055mm).

[0041] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0042] Example 1

[0043] This embodiment provides a cadmium telluride power generation glass with SiO2 film, such as Figure 1 and Figure 2 As shown, the preparation method thereof comprises:

[0044] (1) 13 mL of SiO2 suspension (concentration of 10 wt%) was dropped onto the center of the CdTe power generation glass matrix. After the SiO2 suspension completely infiltrated the surface of the power generation glass matrix, the power generation glass matrix was rotated at a speed of 150 rpm for 60 s, and then the CdTe power generation glass matrix was rotated at a speed of 500 rpm for 90 s to form a SiO2 coating with a thickness of 127 nm (e.g. Figure 1 and Figure 2 as shown).

[0045] (2) The cadmium telluride power generation glass base material is dried at a low temperature of 60°C.

[0046] (3) Using a CO2 laser, the entire SiO2 coating surface of the power generation glass matrix is ​​scanned by a galvanometer for 40 seconds. Figure 3 As shown, the laser 3 generates laser light and controls the movement of the laser light through the galvanometer 2 to irradiate the surface of the base material 1 for processing. The temperature of the SiO2 coating is controlled to be 400-420°C, so that the SiO2 coating is solidified to form a SiO2 film with a thickness of 100nm.

[0047] The parameters of the CO2 laser are: spot width 0.2mm; line filling spacing 0.05mm, and output power 80w.

[0048] Example 2

[0049] This embodiment provides a cadmium telluride power generation glass with a SiO2 film, and the preparation method thereof includes:

[0050] (1) 15 mL of SiO2 suspension (concentration of 10 wt%) was dropped onto the center of the CdTe power generation glass matrix. After the SiO2 suspension completely infiltrated the surface of the power generation glass matrix, the power generation glass matrix was rotated at 200 rpm for 50 s, and then at 600 rpm for 120 s to form a SiO2 coating with a thickness of about 110 nm.

[0051] (2) The cadmium telluride power generation glass base material is dried at a low temperature of 50°C.

[0052] (3) A CO2 laser is used to scan the entire surface of the SiO2 coating of the power generation glass mother material in a galvanometer manner, and the temperature of the SiO2 coating is controlled to be 410-430°C, so that the SiO2 coating is solidified to form a SiO2 film with a thickness of 90nm.

[0053] The parameters of the CO2 laser are: spot width 0.15mm; line filling spacing 0.06mm, and output power 60w.

[0054] Example 3

[0055] This embodiment provides a cadmium telluride power generation glass with a SiO2 film, and the preparation method thereof includes:

[0056] (1) 10 mL of SiO2 suspension (concentration of 10 wt%) was dropped onto the center of the cadmium telluride power generation glass matrix. After the SiO2 suspension completely infiltrated the surface of the power generation glass matrix, the power generation glass matrix was rotated at a speed of 100 rpm for 70 seconds, and then the cadmium telluride power generation glass matrix was rotated at a speed of 400 rpm for 60 seconds to form a SiO2 coating with a thickness of about 200 nm.

[0057] (2) The cadmium telluride power generation glass base material is dried at a low temperature of 100°C.

[0058] (3) A CO2 laser is used to scan the entire surface of the SiO2 coating of the power generation glass mother material in a galvanometer manner, and the temperature of the SiO2 coating is controlled to be 430-450°C, so that the SiO2 coating is solidified to form a SiO2 film with a thickness of 150 nm.

[0059] The parameters of the CO2 laser are: spot width 0.25mm; line filling spacing 0.04mm, and output power 100w.

[0060] Experimental Example 1

[0061] This experimental example uses high temperature baking and high temperature curing of SiO2 coating to explore the curing temperature of SiO2:

[0062] (1) 13 mL of SiO2 suspension (concentration of 10 wt%) was dropped onto the center of the cadmium telluride power generation glass matrix. After the SiO2 suspension completely infiltrated the surface of the power generation glass matrix, the power generation glass matrix was rotated at a speed of 150 rpm for 60 s, and then the cadmium telluride power generation glass matrix was rotated at a speed of 500 rpm for 90 s to form a SiO2 coating with a thickness of 127 nm.

[0063] (2) The cadmium telluride power generation glass matrix is ​​placed on a heating table, heated to 397°C along with the heating table, and then kept warm for ten minutes before conducting a fixation test to test whether high-temperature heating can solidify the suspension.

[0064] The method of fixation test is: rub the surface with an eraser 15-20 times, then wipe the surface with a clean cloth. If there is no trace, it means that the degree of fixation meets the requirements.

[0065] The hardness test method is: use a pencil with a hardness of 2H, 3H, 4H, 5H, or 6H to scratch the surface. If scratches appear, it means that the coating hardness is lower than the pencil hardness.

[0066] The results are as follows Figure 4-6As shown, Figure 4 The adhesiveness test was performed with an eraser but the rubber was not wiped off. Figure 5 After wiping the surface under the microscope, there are no traces; Figure 6 The surface condition is observed by naked eyes, and there are no traces. The test results of the degree of fixation show that when baked at about 400℃, the SiO2 coating on the surface of the power generation glass is initially solidified; and in order to achieve a good curing effect, the heating temperature must be at least greater than 400℃.

[0067] Experimental Example 2

[0068] This experimental example investigates the drying temperature before CO2 laser scanning:

[0069] 1. Experimental process:

[0070] (1) 13 mL of SiO2 suspension (concentration of 10 wt%) was dropped onto the center of the cadmium telluride power generation glass matrix. After the SiO2 suspension completely infiltrated the surface of the power generation glass matrix, the power generation glass matrix was rotated at a speed of 150 rpm for 60 s, and then the cadmium telluride power generation glass matrix was rotated at a speed of 500 rpm for 90 s to form a SiO2 coating with a thickness of 127 nm.

[0071] (2) The cadmium telluride power generation glass base material is placed on a heating table and heated to the temperature shown in Table 1 for drying.

[0072] (3) For different samples, a CO2 laser is used to scan the entire surface of the SiO2 coating of the power generation glass mother material in a galvanometer manner to solidify the SiO2 coating to form a SiO2 film. The CO2 laser scanning parameters are: spot width 0.2mm; line filling spacing 0.05mm, output power 80w.

[0073] (4) Check the surface of the sample to see if there is any damage or cracks.

[0074] 2. Effect test:

[0075] Table 1. Effect of heating temperature on the performance of power generation glass

[0076] Sample number Heating temperature and time Effect 0 Base Material - 1 40℃、1h Sample cracked 2 50℃、1h The sample has no cracks, but the power generation performance is good 3 60℃、1h The sample has no cracks, but the power generation performance is good 4 80℃、1h The sample has no cracks, but the power generation performance is good 5 100℃、1h The sample has no cracks, but the power generation performance is good 6 120℃、1h The sample has no cracks and the power generation performance is poor 7 400℃, 1h, without laser scanning The sample has no cracks, but the power generation performance is poor

[0077] It can be seen from Table 1 that if the method of directly heating to 400°C for curing is adopted, such as sample 7, although a SiO2 coating can be obtained, the circuit on the backlight surface of the power generation glass is damaged during the heating process, resulting in poor power generation performance.

[0078] Comparing samples 1-6, when the heating temperature is too low (40°C), the samples are prone to cracking during the subsequent laser scanning process; when the heating temperature is too high (120°C), although the surface cracks of the samples can be avoided, the circuit on the backlight side of the power generation glass is damaged during the heating process, resulting in poor power generation performance of the samples. When the heating temperature is between 50-100°C, the samples obtained after laser scanning are not only free of cracks, but also have improved power generation performance compared to the parent material.

[0079] Experimental Example 3

[0080] This experimental example examines the parameters of CO2 laser scanning:

[0081] 1. Experimental process:

[0082] (1) 13 mL of SiO2 suspension (concentration of 10 wt%) was dropped onto the center of the cadmium telluride power generation glass matrix. After the SiO2 suspension completely infiltrated the surface of the power generation glass matrix, the power generation glass matrix was rotated at a speed of 150 rpm for 60 s, and then the cadmium telluride power generation glass matrix was rotated at a speed of 500 rpm for 90 s to form a SiO2 coating with a thickness of 127 nm.

[0083] (2) Dry the cadmium telluride power generation glass base material at 60°C for 1 hour.

[0084] (3) For different samples, a CO2 laser is used to scan the entire surface of the SiO2 coating of the power generation glass mother material in a galvanometer manner, so that the SiO2 coating is solidified to form a SiO2 film; the parameters of CO2 laser scanning of different samples are shown in Table 2.

[0085] 2. Effect test:

[0086] (1) Fixation test:

[0087] After rubbing the surface with an eraser 15-20 times, wipe the surface with a clean cloth. If there is no trace, it means that the degree of fixation meets the requirements.

[0088] (2) Hardness test:

[0089] Use a pencil with a hardness of 2H-6H to perform a scratch test. If the hardness reaches 2H-3H, it meets the curing requirements.

[0090] 3. Test results:

[0091] Table 1. Effect of laser scanning parameters on the performance of power generation glass

[0092] Serial number (sample number) Spot width (0.8mm) Pre-baking temperature (℃) Power (W) Line fill spacing Effect 1 0.8 60 95 0.03 Damage, cracks, broken samples 2 0.8 60 90 0.03 No damage, cracks, broken samples 3 0.8 60 85 0.03 No damage, reduced cracks, sample breakage, can be wiped off 4 0.8 60 80 0.03 No damage, reduced cracks, sample breakage, can be wiped off 5 0.8 60 85 0.1 No damage, can be wiped off 6 0.8 60 85 0.08 No damage, some parts can be wiped off 7 0.8 60 85 0.05 No damage, rarely can be wiped off 8 1.5 60 85 0.05 No damage, can be wiped off 9 1.0 60 85 0.05 No damage, can be wiped off 10 0.5 60 85 0.05 No damage, can be wiped off 11 0.2 60 85 0.05 There is slight damage, which cannot be wiped off 12 0.1 60 85 0.05 There is damage, can't be wiped off 13 0.2 60 75 0.05 No damage, can be wiped off 14 0.2 60 80 0.05 No damage, can't be wiped off, scratches 15 0.2 60 85 0.05 The surface is damaged, the sample is cracked, cannot be wiped off, and has scratches 16 0.2 60 90 0.05 Damaged, cannot be wiped off, has scratches 17 0.2 60 95 0.05 The surface is damaged, the sample is cracked, cannot be wiped off, and has scratches

[0093] It can be seen from Table 1 that:

[0094] Through experiments #1-#4, it was found that when the power was 85W, the number of cracks was the least, but due to the high filling density, cracks still occurred and could not be fixed.

[0095] Through #5-#7, it is concluded that when the filling density is 0.05mm, fixation can be achieved with the minimum damage.

[0096] Through #8-#12, it can be concluded that when the spot width is 0.2mm, the fixation degree is the best and the damage is the smallest.

[0097] The best current at the new spot width and filling density was tested through #12-#17. When the power of #14 was 80W, the fixation was the best and there was no damage.

[0098] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing cadmium telluride power generation glass with SiO2 film, characterized in that: It includes: Coating a SiO2 suspension on the light-facing surface of a cadmium telluride power generation glass mother material to form a SiO2 coating, wherein the SiO2 content in the SiO2 suspension is 8-12wt%, and the solvent is ethanol; The cadmium telluride power generation glass base material is dried at a temperature of 50-100° C. for 8-10 minutes; Then, a CO2 laser is used to scan the entire surface of the SiO2 coating of the cadmium telluride power generation glass mother material, and the temperature of the SiO2 coating is controlled to be 400-450° C., so that the SiO2 coating is solidified to form a SiO2 film with a thickness of 90-150 nm; When the CO2 laser is used to scan the entire sheet, the scanning is performed in a galvanometer manner, the output power of the CO2 laser is 60-100w, the spot width is 0.15-0.25mm; the line filling spacing is 0.04-0.06mm; The coating method of the SiO2 coating is: A SiO2 suspension is dropped onto the center of the cadmium telluride power generation glass mother material. After the SiO2 suspension completely infiltrates the surface of the cadmium telluride power generation glass mother material, the cadmium telluride power generation glass mother material is rotated at a speed of 120-180 rpm for 55-65 s, and then the cadmium telluride power generation glass mother material is rotated at a speed of 450-550 rpm for 80-100 s.

2. The method for preparing cadmium telluride power generation glass according to claim 1, characterized in that: The thickness of the SiO2 coating is 100-200nm.

3. The method for preparing cadmium telluride power generation glass according to claim 2, characterized in that: The volume of the SiO2 suspension dropped onto the center of the cadmium telluride power generation glass matrix is ​​10-15 mL.

4. A cadmium telluride power generation glass, which is prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The light-facing surface of the cadmium telluride power generation glass has a SiO2 film with a thickness of 90-150nm.

Citation Information

Patent Citations

  • Method for Laser Curing of Anti-Reflective Coatings

    US20160260848A1